Nitrogen fertilization on topdressing and soil water replacement levels on carrot crop yield - Santana, Márcio José de; Mendonça, Ana Paula Leite de; Silva, Marcos Vinícius Pires; Xavier, Acácio Gomes; Rossi André, Maria Eduarda Rocha (Revista Agrogeoambiental, 2022)
Nitrogen is a fundamental nutrient required in large quantities for carrots, which raises concerns about the right time and doses to be used. Although irrigation is also an essential practice for crop success, the deficit or excess of water can provide unfavorable conditions for the development of carrots. This work was carried out aiming at evaluating the effect of nitrogen fertilization on topdressing and soil water replacement levels on carrot yield. The experiment was conducted at Federal Institute of Education, Science, and Technology of the Triângulo Mineiro (IFTM) – Uberaba Campus, MG, Brazil, in a 4 × 4 factorial and randomized blocks involving four nitrogen doses applied to the topdressing (0 kg ha-1, 42 kg ha-1, 84 kg ha-1, and 126 kg ha-1) and four water replacement levels (70 %, 100 %, 130 %, and 160 %) based on the estimated values of the ETc of the crop. The interaction was significant only for the root diameter variable. Among the results, we can see that the N dose for the 119.4 kg ha-1 topdressing was the one that provided the maximum number of commercial roots, while soil water replacement of 86.94 % induced maximum total productivity.